A Cytotoxic Compound from n-Hexane Fraction of Lantana camara Linn Leaves - Suryati Suryati; Yuni Malasari; Mai Efdi; Elida Mardiah (Molekul, 2019)
In this study, one triterpenoid compound from n-hexane fraction of Lantana camaraLinn leaves has cytotoxic activity was isolated. Isolation was carried out using gravity chromatographycolumnand purification by recrystallization method. Isolated compound was obtained white solid with melting point 252-253oC. The structure of isolated compound was elucidated using spectroscopic analysis Ultraviolet (UV), Infrared (IR), 1H-Nuclear Magnetic Resonance (1H-NMR), 13C-Nuclear Magnetic Resonance (13C-NMR) Heteronuclear Multiple Bond Connectivity (HMBC),  Heteronuclear Multiple Quantum Correlation (HMQC), Distortionless Enhancement Polarization Transfer (DEPT) and comparative literature data, identified as Lantadene A (22β-angeloyloxy-3-oxoolean-12-en-28-oic-acid) with molecule formula C35H52O5. The Lantadene A compound was evaluated for cytotoxic activity against shrimp larvae Artemia SalinaLeach using Brine Shrimp Lethality Test(BSLT) method, showed strong cytotoxic activity with an LC50value of 48.97 µg/mL.